Combined effect of exercise and curcumin on inflammation-associated microRNAs and cytokines in old male rats: A promising approach against inflammaging - Zahra Shargh; Keyvan Asghari; Morteza Asghariehahari; Leila Chodari (Heliyon)
Purpose: Inflammation serves as a key contributor to various diseases, necessitating the discovery of new treatment approaches to address its causative role. Methods: The study involved 35 male Wistar rats, including 7 young rats (3-month-old; 200–250 g) in the Young control group and 28 aged rats (18-month-old; 400–450 g) randomly distributed among the Old control, Exercise, Curcumin, and Exercise + Curcumin groups. During an 8-week period, the Exercise group underwent running on the treadmill (17 m/min), while those in the Curcumin group were supplied with daily curcumin doses (50 mg/kg) through gavage. Upon completion of the study, serum samples from each group were collected for evaluating interleukin-6 (IL-6), interleukin-1β (IL-1β), interleukin-10 (IL-10), and Tumor Necrosis Factor-α (TNF-α) levels using ELISA; malondialdehyde (MDA) by enzymatic assay; and miR-21 and miR-146a by RT-PCR. Results: Our findings revealed that the Old control group, in contrast to the Young control group, showed a significant reduction in IL-10 serum levels, while MDA, TNF-α, IL-1β, and IL-6 serum levels were significantly elevated. Additionally, the expression of inflammatory microRNAs (miRNAs), miR-21 and miR-146a, was significantly enhanced in the Old control rats compared with the Young control group. Exercise and curcumin treatment alone resulted in an improvement in the expression of the markers and miRNAs associated with inflammation. Furthermore, when exercise and curcumin were administered simultaneously, a synergistic effect was observed compared to the exercise or curcumin alone groups. Conclusion: Curcumin and exercise, individually and synergistically in combination, effectively reduced inflammation in aged rats, likely due to decreased oxidative stress and MDA levels mediated by miR-21 and miR-146a downregulation.